TAZKIYAH AL-NAFS SEBAGAI TERAPI DALAM PERMASALAHAN MASYARAKAT MODERN - Abdi Rizal (Universitas Islam Negeri Imam Bonjol Padang, 2022)
Man is a creature of God who was made as caliph of God on this earth. In order to become a caliph or messenger of God on this earth, people must always strive to purify themselves or their souls must be clean from all reprehensible actions. Thus, a soul that has been dirty and far from praiseworthy deeds will not reach union with the Creator. The term for the purification of the soul in the study of Sufism is Tazkiyah An-Nafs. To get closer to God, people must first purify their souls. This type of research is literature research using primary data sources and secondary data. The results of this research explain that in order to get closer to God, humans must first purify their souls through three steps, namely takhalli, tahalli and tajalli. By carrying out the three processes above, humans will achieve soul purification and unite with the Creator. Furthermore, this Tazkiyah An-Nafs can also be used as a therapy in all problems that occur in modern society. This can be seen in acts of patience, repentance, contentment and so on.